Inovasi Men’s Fashion: Pengaplikasian Teknik Arsir Silang pada Ilustrasi Relief Candi Menggunakan Digital Printing - Damayanti, Putri; Suhartini, Ratna (BAJU: Journal of Fashion and Textile Design Unesa, 2024)
This research is to find out the process of men's shirts using the idea of ​​the Surowono temple relief by combining elements of traditional art with modern technology to create a unique and interesting product. Inspired by the relief which depicts the story of a stork's neck being clamped to death by a crab. Using cross-hatching techniques to make illustrations have a unique and bold appearance. Then the illustrations are printed using digital printing techniques. The use of digital printing makes it possible to print temple relief illustrations with a high and accurate level of detail on men's shirts. The method used is the double diamond model which consists of 4 stages discover, define, develop and deliver. The process starts with making a moodboard as a source of ideas, making illustrations, then applying the motif to the shirt design and then a product prototype. The results of the research are a cross-hatched illustration and a men's shirt with a temple relief motif that was applied digitally using a cross-hatched technique that has clear detailed motifs. It is hoped that this research will contribute to expanding the boundaries of menswear design, combining traditional elements with modern technology. The resulting product is expected to attract the interest of consumers who are looking for clothing with unique and different characteristics.